Study on the Meshing Force and Meshing Rigidity of Cylinder Sine Oscillation Tooth Transmission - Zeng Yunyun; Yuan Xinmei; Zhou Sizhu (Jixie chuandong)
Based on the hypothesis of stretch small distortion and distortion congruity,the model and algorithm of meshing force analysis under theoretical conditions are given.According to the Hertz theory and geometric relation of meshing pair,the meshing rigidity models of the meshing pair are established,and the calculation formulas of the meshing rigidity and the principal curvature of the contact point are deduced.The presented methods is illustrated through an example,and the distributing characteristic of meshing forces,sum of principal curvature and meshing rigidity of this type of transmission device is acquired.The acquired result can be adopted as the analytical base for structure design,vibration analysis.